Does treatment have an impact on incidence and risk factors for autism spectrum disorders in children with infantile spasms?. (5th May 2015) - Bitton, Jonathan Y.; Demos, Michelle; Elkouby, Katia; Connolly, Mary; Weiss, Shelly K.; Donner, Elizabeth J.; Whiting, Sharon; Ronen, Gabriel M.; Bello‐Espinosa, Luis; Wirrell, Elaine C.; Mohamed, Ismail S.; Dooley, Joseph M.; et al.
Summary Objective Infantile spasms (IS) are a severe form of childhood epilepsy associated with autism spectrum disorders (ASD) in up to 35% of cases. The objective of this post hoc analysis of our randomized control trial was to determine whether rapid diagnosis and treatment of IS could limit the incidence of ASD while identifying risk factors related to ASD outcome. Methods Patients with IS were randomized in a standardized diagnostic and treatment protocol. Clinical and electroencephalogram (EEG) evaluations were completed at all eight visits over 5 years, while cognitive evaluations were administered at 0, 6, 24 and 60 months, respectively. Autism was initially screened by means of the Checklist for Autism in Toddlers (CHAT) at 24 months, and formally assessed at the 30‐and 60‐month follow‐ups using the Autism Diagnostic Observation Schedule—Generic (ADOS‐G). Results Of the 69 patients included in the study, 25 could not be assessed due to severe delay or death. Eleven of the 42 patients screened with CHAT, were found to be at risk of an ASD outcome. ADOS was performed in 44 and 10 were diagnosed with ASD. The CHAT proved to correlate highly with the ADOS (80% ppv). Only patients with symptomatic IS developed ASD (p = 0.003). Earlier diagnosis or successful treatment did not correlate with a reduced rate of ASD. Other risk factors were identified such as having chronic epileptic discharges in the frontotemporal areas after disappearance of hypsarrhythmia (p = 0.005 and p = 0.007) and being of nonwhite origin (p = 0.009). Significance ASD was only observed in children with sympyomatic IS. Other clinical risk factors include chronic frontotemporal epileptic activity and being of non‐white origin. Early diagnosis and treatment did not prevent ASD as an outcome of IS. However, patients at risk for ASD could be identified early on and should in the future benefit from early intervention to potentially improve their long‐term outcome.